Pencils of Euler Triples, II - Čerin, Zvonko (Sarajevo Journal of Mathematics, 2024)
In this second part of the paper we will continue to study the families of triples $(u,v,w)$ of elements in a commutative ring $R$ with the property that ... 2000 Mathematics Subject Classification. Primary 11B37, 11B39, 11D09